ANALISIS KENDALA DAN PERCEPATAN PENYELESAIAN STUDI MAHASISWA JURUSAN AKUNTANSI - Fachrurrozie Fachrurrozie; Kiswanto Kiswanto; Asrori Asrori (Jurnal Pendidikan Ilmu Sosial, 2018)
ABSTRACT The unsuccessfulness of graduating on time is being a problem for many students in all universities. The diversity of the students’ characteristic in the learning process makes them have own strategy to complete their study. However, the key for graduating on time is not only about the students’ activeness in the lecture but also how the students’ capability in finishing their thesis as final project. Therefore, many factors (intern and extern) affect the time needed by students to complete their study.The research aimed to: (1) indentify the obstacles of graduating the study on time in the accounting department of economic faculty in Universitas Negeri Semarang (UNNES), Indonesia; (2) identify the commitment to fulfilling the requirements for graduate for whom that should have been finished; (3) analyze the obstacles factor from campus; (4) analyze the external that hamper the students to graduate; (5) Find out the students efforts to complete their study; (6) understand the students’ expectation to the department administrator for completing their study; and (7) determine the solution for students who have problems in order to graduate from the university. The survey approach was used with the students of accounting department of UNNES who late to complete their study as the source persons.